Evaluasi Program Merdeka Belajar Kampus Merdeka di Universitas Tadulako - Anggraeni, Intan Kusuma; Kurnia, Intam; Ferianto, Fiki (JPS: Journal of Publicness Studies, 2025)
Merdeka Belajar Kampus Merdeka is a program of the Minister of Education and Culture in order to prepare students to master various scientific fields as preparation for facing the world of work. This research is an evaluation research type that aims to evaluate the Merdeka Belajar Kampus Merdeka (MBKM) program within the scope of Tadulako University using the CIPP Model (Context, Input, Process and Product) developed by Stufflebeam, consisting of four components with a research design. The total informants in this study were 12 people consisting of 10 active students who had participated in the MBKM program, especially MSIB in the last two periods, the Head of the University MBKM and the PIC MSIB of the University. The results of the study showed that the evaluation of the MBKM program at Tadulako University had not been fully maximized, the distribution of basic facilities in the form of MBKM implementation guidelines that were not inclusive, knowledge and understanding related to the program were still lacking, and the curriculum in the study program was considered not yet adaptive, resulting in the target achievement of the Indikator Kinerja Utama (IKU) not being fully achieved. Although the context component has shown alignment between the program objectives and strategies formulated as a form of readiness in terms of both planning and implementation, this has not been optimal in implementing the MBKM program.